An Exploration Of Mothers’ Experiences Of Feeding Shredded Monasprest To Under-Five Children - Pramitha, Putri Widya; Munif, Badrul; Firmanti, Tria Anisa (Poltekkes Kemenkes Semarang, 2024)
Background: The role of parents as early as possible influences the child's growth and development later in life, especially the role of the mother during the critical period of the first 1000 days of life. Good maternal knowledge and care are positively related to the quality of child care, including children's eating habits.Purpose: This study aims to explore mothers' experiences of feeding shredded monasprest to children under-fives years old (baduta).Methods: The research design in this study was qualitative with a phenomenological method. There were 9 participants in this study, participants were not directed at number, but based on coverage until data saturation was reached. The sampling technique used purposive sampling in accordance with the inclusion criteria. The data collection tools used in this research were the researchers themselves with in-depth interview guidelines, field notes and recording equipment. The data in this study were analyzed using the Colaizi method.Results: The results of this research gave rise to two themes and in each theme, there were two sub-themes, namely the baduta's response when given Monasprest floss food and the response of the baduta's mother when giving Monasprest shredded food.Conclusion: This research shows that the response of toddlers when given monasprest shredded food increases the baduta's appetite and increases the frequency of eating with monasprest shredded food. As well as the response of the baduta mothers when giving the monasprest floss food, namely their interest in flossed monasprest and the mother's knowledge.